MEDIA OPTIMIZATION FOR INORGANIC PHOSPHATE SOLUBILIZING BACTERIA ISOLATED FROM ANAND ARGICULTURE SOIL.: Life Science-Botany - SAGERVANSHI, AMIT; KUMARI, PRIYANKA; NAGEE, ANJU; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Phosphorus (P) is one of the essential macronutrients for plant growth and reproduction. Plants acquire P from the soil solution as phosphate anions. However, phosphate anions are extremely reactive and may be immobilized through precipitation with cations such as Ca2+, Mg2+, Fe3+ and Al3+, depending on the particular properties of the soil and as a result, the phosphate is highly insoluble and unavailable to plants. Application of phosphate-solubilizing fungi (PSF) has been added as fertilizer to increase P uptake and plant growth. The improvement of soil fertility is one of the most common strategies to increase agricultural production. Maintaining high levels of available nitrogen (N) and phosphorus (P), the two most limiting nutrients in soil, remains big challenge. The present paper provides details about the different media used to get more phosphate solubilizing using isolated bacterial strains.